Contactless switch for controlling loads - Adnan, Muhamad Mursayidi; Mohammad, Nurul Nadia; Azli, Shakira Azeehan; Abd Hamid, Fatimah Khairiah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
In recent years, the growing demand for automation and remote-control systems has revolutionized the way we manage electrical devices, offering unparalleled convenience and efficiency. Among the emerging innovations in this field is contactless switching technology, which allows users to control electrical loads without the need for physical interaction with traditional switches. This breakthrough not only enhances convenience but also significantly improves safety and accessibility in various environments. Conventional switches for controlling electrical loads often come with significant limitations and challenges, primarily requiring physical contact for operation. This design can be inconvenient, unhygienic, or even unsafe in specific environments such as hospitals or kitchens. Additionally, individuals with limited mobility or disabilities may struggle to operate standard switches, limiting their independence and accessibility. These inefficiencies and drawbacks underscore the need for innovative alternatives like contactless switching. Moreover, an accessible solution for individuals with disabilities or mobility challenges, enabling them to control electrical devices effortlessly. By incorporating technologies such as infrared and radio frequency, this project aims to showcase the feasibility and practicality of contactless control in real-world applications. This initiative highlights the potential of contactless switching to transform everyday interactions with electrical systems, paving the way for smarter, safer, and more accessible solutions in automation. The adoption of contactless switches marks a significant step toward safer, more convenient, and inclusive solutions for managing electrical systems in various settings.